Metacognitive Change During Exposure and Metacognitive Therapy in Obsessive-Compulsive Disorder - Hansmeier, Jana; Haberkamp, Anke; Glombiewski, Julia A.; Exner, Cornelia (Frontiers in Psychiatry, 2021)
Metacognitive therapy (MCT) has been shown to be a promising treatment approach for obsessive-compulsive disorder (OCD). The changeability of metacognitions by (metacognitive) treatment and its relevance to treatment outcome is, however, still unclear. The current study investigates, (1) if treatment with MCT or exposure and response prevention (ERP) in a randomized-controlled pilot trial (n = 24 patients with OCD) changes OCD-specific metacognitions of thought fusion beliefs, beliefs about rituals and stop signals, and (2) if these changes are relevant for the treatment outcome in terms of patient- and therapist-rated OCD symptoms. ANOVA with pretest, posttest and follow-up scores could show that all three metacognitions significantly decreased during both treatments. Regarding thought fusion beliefs, a significant interaction effect indicated a higher decrease after MCT than ERP treatment. In hierarchical regression analyses, changes in stop signals from pre- to post-treatment significantly predicted patient-rating OCD symptoms at post-treatment and follow-up at three months after treatment. These changes were even predictive of post-treatment outcome after controlling for general metacognitions and dysfunctional cognitive beliefs. These findings support the assumption that metacognitions can change during both treatments and that changes in stop signals might be relevant for the treatment outcome on the symptom level in OCD.